Gammarid amphipods (Crustacea) in Norway, with a key to the species - Vader, Wim; Tandberg, Anne Helene Solberg (Fauna norvegica, 2019)
Thirteen species in the amphipod family Gammaridae have been reported from Norway. This paper gives a survey of the distribution and habitat of all 13 species of the family Gammaridae occurring or expected to occur in Norwegian waters: both marine, brackish and fresh, including Svalbard, in addition to four species found in close neighbouring waters. It also provides a short history of the study of Gammaridae in Norway, as well as an illustrated identification key to all species in the area. publishedVersion